Tranceiver Multi Channels Untuk Kontrol Gerak dan Monitoring Kondisi Pada Robot Manual Mini Industri - Aad Hariyadi; Yani Ratnawati; Ridho Hendra Yoga Perdana (Jurnal IPTEK, 2020)
Robotic technology that is developing rapidly triggers robotics developers to improve their abilities, especially in the field of robot control and monitoring. Today, robots are indeed present in human life in various forms. One type of robot that is often developed by robotics developers is the Industrial Mini Manual Robot. An industrial mini manual robot is a transporter robot that is equipped with a gripper and is controlled manually by the user through a joystick controller both wired and wireless. The manual robot with cable joystick control is very inefficient in its use so research on wireless joysticks is carried out. However, the current wireless joystick still uses the single-channel method, thereby eliminating multitasking capabilities such as those of the wired joystick robot. In this research, the design of multichannel transceivers for control and monitoring so that the robot has the ability to multitasking and the movement of the robot is not disturbed by wires. Multichannel transceivers use different frequency channels to transmit data. The command data and monitoring data can be transmitted simultaneously. This multi-channel transceiver has an average pairing time of 23.59 ms, a range of 116 meters in each channel and large power consumption of 59 mA.